OPTIMAISASI PENDAPATAN PETANI PADI PADA DIVERSIFIKASI USAHA DI DESA SUKARAJA KECAMATAN BUAY MADANG KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2016)
East OKU District In terms of production of paddy farmers who rely on irrigation networks many farmers in the village although it is a rainfed farmers. Due to the narrowing of farmland pengahasilan production of rice farming alone is not sufficient to meet the needs of farmers' lives and because the average in the village has two harvests in a year, so many farmers are diversifying the business to earn income outside the farming rice. Narrowing of the land and the times giving ideas to diversify its business. Business diversification is one of the main programs of agricultural development. Program development of farm diversification in paddy fields associated with efforts to increase revenues, expansion of employment opportunities and poverty reduction, is one option the right strategy. Diversification is done is diversify the types of business or agricultural crops to avoid dependence on any of the results of operations or agricultural produce as well as minimize the risk of crop failure, then other commodities will cover or reduce the loss suffered by the rice farmers. diversification of farming by the farmers in the village of Talbot namely rice farming and business diversification swallow, rice farming and business diversification fish (catfish), diversification of rice farming and vegetable farming (chickpeas) and diversification of rice farming and rubber farming. the purpose of this study was to mengnalisis "Optimizing Penadapatan Paddy Farmers On Diversification in Talbot Village Madang subdistrict Buay East Ulu Ogan Ogan. Research results show that revenue optimization model of rice farmers in diversification efforts, namely: diversification 1 (rice-swallow) Z = 9.8315 million X1 + X2 19,299,999, diversification 2 (rice-fish) Z = X1 + 10 297 8.746 million .000 X2, business diversification 3 (rice-vegetable) Z = 5.6295 million 4.415 million X1 + X2, business diversification 4 (rice-rubber) Z = 10.702 million X1 + X2 4.1755 million. The amount of optimal income of rice farmers in business diversification, namely: the diversification of businesses 1 (rice-swallow) Z = 29.1305 million, - the diversification of business 2 (rice-fish) Z = 19,007,006.299 on business diversification 3 (rice-vegetable) Z = 8,301,257.485 and the diversification 4 (rice-rubber) Z = 14.8775 million, -. The income of rice farmers received after scenarios on business diversification is at skenario1 income earned Rp. 32,002,144.888,-. In scenario 2 the income earned Rp. 20,479,007.874, -. On 3 skenerio income earned Rp. 9,279,431.138, -. And at 4 skenerio income earned Rp. 15,610,561.37, -.